2019
DOI: 10.1002/solr.201900095
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Passivation Effects of Na and K at Grain Boundaries in Polycrystalline Cu(In,Ga)Se2 Thin Films for Solar Cells

Abstract: Thin‐film solar cells based on Cu(In,Ga)Se2 (CIGSe) absorber layers reach conversion efficiencies of above 20%. One key to this success is the incorporation of alkali metals, such as Na and K, into the surface and the volume of the CIGSe thin film. The present work discusses the impact of Na and K on the grain‐boundary (GB) properties in CIGSe thin films, i.e., on the barriers for charge carriers, Φb, and on the recombination velocities at the GBs, sGB. First, the physics connected with these two quantities as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…In contrast, band-gap fluctuations of 40–45 meV decrease the V oc by about 30 mV. Moreover, enhanced recombination at GBs decrease the V oc and FF of the device (compared with their theoretical limits) substantially, although rather low, average (effective) recombination velocities at GBs of several 100 cm s −1 are determined (as compared with values of several 1000 cm s −1 measured on Na/K-free or Na/K-containing CIGSe layers without any subject to RbF PDT 39 . It will be matter of future studies to reveal whether these low S GB values can indeed be traced to a passivation effect of Rb at CIGSe GBs.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In contrast, band-gap fluctuations of 40–45 meV decrease the V oc by about 30 mV. Moreover, enhanced recombination at GBs decrease the V oc and FF of the device (compared with their theoretical limits) substantially, although rather low, average (effective) recombination velocities at GBs of several 100 cm s −1 are determined (as compared with values of several 1000 cm s −1 measured on Na/K-free or Na/K-containing CIGSe layers without any subject to RbF PDT 39 . It will be matter of future studies to reveal whether these low S GB values can indeed be traced to a passivation effect of Rb at CIGSe GBs.…”
Section: Discussionmentioning
confidence: 72%
“…In this respect, we would like to note that Siebentritt et al 38 reported evidence for the passivating effect of K, Rb, and Cs at GBs (via the reduction of barriers Φ b for charge carriers), while Abou-Ras et al 39 , using CL analyses, did not confirm that a KF PDT of CIGSe surfaces leads to passivation of the GBs in these absorber layers (i.e., the effective recombination velocities S GB,eff remain at about the same level with and without the KF PDT). This discrepancy can be traced back at least in part to the fact that Siebentritt et al applied surface-sensitive scanning Kelvin-probe force microscopy for the measurement of the barriers heights Φ b at the GBs and that GB properties at the very surface of a CIGSe layer need not be the same as in the CIGSe bulk.…”
Section: Discussionmentioning
confidence: 95%
“…More recent studies, where a KF-PDT was applied indicate also accumulation of K at GBs 29,30 . As a consequence of the relative concentrations of the different alkali elements at GBs and in the grain interior, several effects have been observed 31 , including Cu depletion, In and Se accumulation at GBs 32 , a diminished downward 33 and increased upward 16 band bending at GBs, increase 3436 or decrease 10 of carrier concentration, and an impact on the GB recombination velocity 37 . A similar range of observations has been reported for RbF-PDT 3841 .…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] Although mainstream principles have been elucidated, there is still much debate on how alkali doping leads to performance improvement. [33] We fabricated a CZTSSe solar cell with an FF of over 60% on a flexible metal substrate and used it to analyze the effects of Na doping. From the results, we postulate that the carrier transport path depends on the amount of Na dopant, which affects the electrical resistance and FF of the polycrystalline CZTSSe solar cells.…”
Section: Introductionmentioning
confidence: 99%